Strengthening Indonesia's Open Proportional Electoral System: A SOAR Analysis for 2024 Implementation Strategy - Milwan, Milwan; Sunarya, Amud; Akadira, Tora (Yayasan Ilomata, 2025)
This research investigates the enhancement of Indonesia's Open Proportional Electoral System (OPES) through a SOAR (Strengths, Opportunities, Aspirations, Results) analysis to strategize its implementation for the 2024 elections. Utilizing a comprehensive literature review method, the study analyzed 984 articles from Google Scholar and 1000 from Crossref, narrowing down to eight pertinent studies published within the last three years. The SOAR analysis revealed key strengths of the OPES, including increased political plurality and direct voter engagement, while identifying opportunities for reform, such as reducing campaign financing and mitigating money politics. The aspirations highlighted a desire for greater accountability and integrity in electoral processes. Results indicated that implementing measures to limit campaign expenditures and enhance transparency could significantly reduce electoral misconduct. The study recommends establishing stricter regulations on campaign financing and fostering public awareness campaigns to educate voters on their rights and the electoral process. By addressing these challenges and leveraging existing strengths, Indonesia can strengthen its democratic practices and ensure a more equitable electoral landscape in the upcoming elections. This analysis provides a structured framework for policymakers to navigate the complexities of electoral reform effectively.